PENGARUH KOMPENSASI TERPERSEPSI DAN LINGKUNGAN KERJA TERPERSEPSI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI MEDIASI (STUDI PADA PT. PISMA GARMENT INDO DEMAK) - Nonik Maelani, 13.05.51.0150 (Students' Journal of Economic and Management, 2017)
The purpose of this study is to analyze the effects of perceived compensation and perceived work environtmenton the job performance with motivation as mediator in PT. Pisma Garment Indo Demak. The independent variable that are presumed to affect the job performance in this study is restricted to compensation and work environtment with motivation as the mediating variable. The population in this study is employees of PT. Pisma garment Indo demak which amounts to 250 people.this study use random sampling method Samples are taken at random, regardless of the extent of the population. This study using statistical test that include validity test with factor analysis,reliability test using Cronbach’s alpha, double regression analysis, and significance test using the coefficient of determination to prove the validity of hypothesis and for mediation test. The result of this study correctly proved that model’s ability to explain correctly, perceived compensation variable’s influence, perceived work environtment and motivation to job performance is amounted 55 %. Whereas the other’s is amounted 45% as explained by variables outside the data-model. Mediating effect test proved that the effect of compensation and work environtment on the job performance are mediated by motivation. Keywords : perceived compensation, perceived work environtment, motivation and job performance